2017
DOI: 10.1186/s12917-017-1055-y
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella serotypes and their antimicrobial susceptibility in apparently healthy dogs in Addis Ababa, Ethiopia

Abstract: BackgroundThe close bond between pet animals and family members poses risk of infection with zoonotic bacterial pathogens such as Salmonella. No data is available on occurrence of Salmonella in dogs in Ethiopia. The aim of this study was therefore to determine the prevalence, serotype distribution and antimicrobial resistance of Salmonella from feces of apparently healthy dogs in Addis Ababa, Ethiopia.ResultsOf the total 360 dogs examined, 42 (11.7%; 95% Confidence limit of 8.5%–15.4%) were positive for Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 31 publications
4
35
3
2
Order By: Relevance
“…Although the majority cases in humans are foodborne [41], there is an increase concern regarding the role of pets as reservoirs for nontyphoidal Salmonella [42,43]. In the present study, 15.2% (7/46) dogs fed RMBD shed Salmonella enterica, including S. Typhimurium, S. Heidelberg, and S. Saintpaul, which are frequently associated with human salmonellosis [44,45]. Conversely, only one dog (1/192 = 0.5%) fed commercial dry feed was positive for Salmonella spp.…”
Section: Salmonella Sppmentioning
confidence: 55%
See 2 more Smart Citations
“…Although the majority cases in humans are foodborne [41], there is an increase concern regarding the role of pets as reservoirs for nontyphoidal Salmonella [42,43]. In the present study, 15.2% (7/46) dogs fed RMBD shed Salmonella enterica, including S. Typhimurium, S. Heidelberg, and S. Saintpaul, which are frequently associated with human salmonellosis [44,45]. Conversely, only one dog (1/192 = 0.5%) fed commercial dry feed was positive for Salmonella spp.…”
Section: Salmonella Sppmentioning
confidence: 55%
“…Additionally, three Salmonella enterica of serovars S. Typhimurium, S. Panama, and S. Saintpaul, from dogs fed RMBD, were multidrug resistant (resistant to three or more antimicrobial classes, according to Sweeney et al [49]). It is interesting to note that this resistance pattern included antimicrobials that are largely used for human and veterinary medicine, such as oxytetracycline, streptomycin, and trimethoprim/sulfamethoxazole [44]. Additionally, one Salmonella spp.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on antimicrobial drug susceptibility of Salmonella isolates from household dogs in Ethiopia showed resistance rates varying from 26% to 60% for amoxicillin‐clavulanic acid, ampicillin, cephalothin, streptomycin, neomycin and oxytetracycline; with 50%, and 60% for the last two drugs (Kiflu et al . ). These findings seem to show that drug resistance of Salmonella from dogs can vary widely depending on the geographic area and possibly, serovars.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of apparently healthy dogs conducted decades ago identified many different serovars and carrier rates from 4 to 16% (Morse et al 1976;Shimi et al 1976). More recent information on the carrier state in dogs is available from the United States (Jay-Russell et al 2014; Leahy et al 2016;Reimschuessel et al 2017), Ethiopia (Kiflu et al 2017), the United Kingdom (Philbey et al 2014), Thailand (Srisanga et al 2016), Taiwan (Tsai et al 2007), Turkey (Kocabiyik et al 2006;Bagcigil et al 2007), Trinidad (Seepersadsingh et al 2004) and Germany (Weber et al 1995). This study was conducted to determine the prevalence and serovars of non-typhoidal Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%